Meningkatkan Hasil Belajar Matematika Menggunakan Media Congklak Siswa Kelas IV MI Al-Hadi II - Putri, Alfianti Kusuma; Kurniawati, Wahyu (Universitas Muhammadiyah Magelang, 2024)
This study aims to improve the mathematics learning outcomes of FPB and KPK materials through concrete media in the form of congklak in grade IV students of MI Al-Hadi II. The type of research used is Classroom Action Research. The subjects of this study were 20 students of grade IV MI Al-Hadi II. This research consists of two cycles. Each cycle goes through four stages: planning, action, observation, and reflection. Data collection in this study used test, observation, and documentation techniques. The data analysis technique used is quantitative descriptive. The results showed that the use of congklak media can increase the average score of students, the percentage of students whose learning outcomes have not been completed at the pre-cycle stage is 60% with an average score of 72.25. There is a cycle I has increased, namely those who achieve KKM scores there are 60% with an average of 76 or 12 out of 20 students have reached KKM. In cycle 2 there was a significant increase with a percentage of 90% and an average value of 79. These results show that the application of congklak media makes students experience an increase in mathematics learning outcomes of FPB and KPK materials.